Carotid intimal-medial thickness in active professional American Football players aged 23 to 35 years - Hurst, R. T.; Nelson, M. R.; Kendall, C. B.; Cha, S. S. (The American Journal of Cardiology, 2012)
Risk of cardiovascular disease and death in retired professional American football players may be higher than that in the general population. Previously published data have demonstrated that American football players have less glucose intolerance, less smoking, similar lipid profiles, and higher blood pressure despite a much larger body compared to the general population, although the presence of subclinical atherosclerosis in these subjects has not been evaluated. This study compared the prevalence of subclinical atherosclerosis in active professional American football players to that in age-, gender-, and race-matched controls derived from the Bogalusa Heart Study. Carotid intimal-medial thickness (CIMT) was used as an indicator of subclinical atherosclerosis in 75 active American football players (23 to 35 years old, 31 white, 44 African-American) as measured by B-mode ultrasonography at Mayo Clinic, Scottsdale, Arizona, on September 13 and 14, 2009. CIMT measurements of 75 athletes were compared to those of 518 matched controls who had CIMT determinations in 1995 and 1996. Two-group t tests determined population similarities between groups. In a generalized linear model, players (overall and by race) had lower CIMT values than controls after age and race adjustment (p <0.001 for all comparisons). Nonlinemen and linemen had lower CIMT values than controls (p <0.001 and p = 0.004, respectively). In conclusion, active professional American football players, regardless of position, had mean CIMT values similar to or lower than those in a matched general population cohort, suggesting that if the prevalence of subclinical atherosclerosis is increased in retired professional American football players, this occurs after retirement.